THE EFFECT OF BOARD RISK MANAGEMENT ON FINANCIAL PERFORMANCE OF SELECTED SACCOS IN KIRUHURA DISTRICT, UGANDA - Kyabarongo Benon; Agaba Moses; Munyabonera Francisis; Eliab Byamukama Mpora; Kikawa Cliff; Ahabwe Oliver fauzi (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The cornerstone of caution in SACCO practice is corporate risk management, and important ideas among SACCOs in Uganda are board risk management and financial performance. The study's goal was to examine how board risk management affected the financial results of particular SACCOS in the Kiruhura District. This study used a cross-sectional survey research design using a quantitative research methodology. The sample size consisted of 184 respondents, staff and members from the six SACCOs registered in the Kiruhura area of Uganda as of January 2023. A total population of 342 persons was used at a confidence level of 95% or error of 0.05. Two stages separated the data that was collected for analysis. First, SPSS version 20.0 was used to conduct the preliminary data analysis and descriptive statistics on the respondents. In the second phase, structural equation modeling (SEM) was used to evaluate and investigate the structural relationships between the variables in the proposed conceptual model. These statistics included multicollinearity, mean and standard deviation, outliers and extreme values, and missing data. SEM was implemented using Jaffrey's Amazing Statistical Program (JASP) version 0.17.2.0. The study's conclusions were: The financial management of savings and credit co-operative societies (SACCOs) in Uganda was found to be significantly positively impacted by board risk management (BRM) (=1.322**), boosting Ha, The study concludes that SACCOs would experience greater financial gains or better financial performance if they are more stringent about the processes they follow to review their risk profile and the policies they put in place. The study recommends that;SACCOs risk management committees of the board should be very effective in influencing the corporate risk management practices adopted within the SACCOs and that SACCOs should improve on the levels of BRM to achieve favorable financial results by applying careful attention to governmental regulations, rules and policies.